Association between the number of convenience stores and caries status in permanent teeth among elementary school children: results from the A-CHILD population-based longitudinal cohort study - Nawa, Nobutoshi; Nishimura, Hisaaki; Matsuyama, Yusuke; Doi, Satomi; Isumi, Aya; Fujiwara, Takeo (Frontiers in Public Health, 2023)
Background In Japan, people have rich access to 24-h convenience stores where they can buy sweets, juice and fluoride hygiene products, among others. However, the association between the number of convenience stores in a neighbourhood and caries in elementary school children status has not been studied. This study aimed to investigate this particular association. Methods Data were derived from a population-based longitudinal cohort study (A-CHILD study) of elementary school children from first-grade to fourth-grade in Adachi City, Tokyo. Caregivers were asked to complete a questionnaire in 2015, 2016, and 2018. A total of 3,136 caregivers provided a valid response. We analysed the association using multilevel Poisson regression. Results The mean number of caries among children in school districts with low, middle, and high number of convenience stores was 0.31 (SD: 0.81), 0.21 (SD: 0.69), and 0.16 (SD: 0.58). After covariate adjustment, children in the school districts with high and middle number of convenience stores had 44% (mean ratio 0.56, 95% CI: 0.31, 0.998) and 31% (mean ratio 0.69, 95% CI: 0.42, 1.13) fewer caries in their permanent teeth, respectively, than children in the school districts with low number of convenience stores. We also found dose–response relationship (p for trend: 0.042). Conclusion Higher number of convenience stores in a school district was associated with fewer caries in permanent teeth among elementary school children. Further study elucidating the mechanism on this protective association is warranted.